The Tanana chiefs: native rights and western law - Schneider, William, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2018)
At the turn of the twentieth century, life was changing drastically in Alaska. The gold rush brought an onslaught of white settlers to the area, railroad companies were pushing into the territory, and telegraph lines opened up new lines of communication. The Native groups who had hunted and fished on the land for more than a century realized that if they did not speak up now, they would lose their land forever. This is the story of a historic meeting between Native Athabascan leaders and government officials, held in Fairbanks, Alaska in 1915. It was one of the first times that Native voices were part of the official record. They sought education and medical assistance, and they wanted to know what they could expect from the federal government. They hoped for a balance between preserving their way of life with seeking new opportunities under the law. The Tanana Chiefs chronicles the efforts by Alaska Natives to gain recognition for rights under Western law and the struggles to negotiate government-to-government relationships with the federal government. It contains the first full transcript of the historic meeting as well as essays that connect that first gathering with the continued efforts of the Tanana Chiefs Conference, which continues to meet and fight for Native rights.--Provided by publisher.
From fur to gold -- From native to white man's country -- The Tanana chiefs meeting of 1915 -- Will Mayo on the Tanana chiefs' meeting -- The Fester -- Appendices -- Introduction to the transcript of the Tanana chiefs' meeting -- The Tanana chiefs meeting transcript -- The Alaska Purchase, a group discussion with William Schneider, Kevin Illingworth, Natasha Singh, and Will Mayo -- Timeline of important events in Native history -- The evolution of this story: reflections on how the past can inform the present.
Keywords: Tanana Indians -- Government relations; Tanana Indians -- Legal status, laws, etc. -- Alaska; Tanana Indians -- History; Wickersham, James, 1857-1939 -- Relations with Indians